Forest certification and economic insights: a European perspective - Corticeiro, Sofia; Brás, Gonçalo; Tomé, Margarida; Lillebø, Ana; Vieira, Helena (Frontiers in Forests and Global Change, 2024)
In recent years, there has been an increasing demand for forest certification and certified forest products in Europe. This trend is related to major worldwide challenges, such as the need to decarbonize the economy and mitigate climate change but also social and consumer demands for wider fair trade. However, whether forest certification influences economic valorization in forestry remains a question. The aim of this study is to analyze forest certification levels across Europe and identify potential relationships between the level of certification in forest areas and relevant economic indicators at country level.This study collected openly available data on total and certified forest areas, economic indicators, and environmental indicators for 28 European countries and explored the correlation between certified forest areas and economic performance in the forestry sector.Findings show that forest certification can significantly improve the economic performance of European forests. It has a more pronounced positive effect on economic incomes than on costs' reduction. While certification costs do rise with the extent of forest area, they tend to stabilize at larger scales, suggesting that the certification process is economically sustainable and scale is relevant. Czechia and the Netherlands stand out for having the highest net values added related to forest certification, reflecting an effective economic exploration of forest resources.This study offers new perspectives to natural and social scientists, as well as to industry and policy makers, by proving contextualized data to support decision making. Additionally, it provides hints for further studies and policy guidelines on sustainable development and the impact of forest certification schemes.